Investigating and analyzing the non-verbal language of the body in the sermons of Nahj al-Balaghah - Mohammad Ghafourifar; Ail Reza Hosseiny; Mahnaz Ghassabi (Religion & Communication)
An important part of everyday human communication is based on non-verbal language and a large number of communication concepts in interpersonal and public interactions through pauses, glances, gestures, facial expressions. And ... it is exchanged that it is called extra-linguistic actions. Non-verbal language is very important because it is the source of people's first perceptions of each other, and a large percentage of people's judgments about each other are based on facial expressions, movements, gestures, physical appearance, and so on.. Among the texts that deserve to be examined is the non-verbal language of the body, the sermons of Nahj al-Balaghah. These sermons are a treasure trove of Arabic literature that has attracted the attention of many thinkers and writers. This study tries to examine the elements of non-verbal language of the body in the sermons of Nahj al-Balaghah and the degree of coherence of these elements with the concepts intended by the Imam in a descriptive-analytical way and from this perspective to present a beautiful analysis of the sermons . Research shows that facial and hand movements are the most efficient and most common types of nonverbal communication used in Nahj al-Balaghah sermons. Non-verbal language of other body parts includes: face color, head movement and foot movement Be; The functions of the non-verbal language of the body in the sermons of Nahj al-Balaghah have been conscious and to convey moral and educational messages.